Effect of Bulb Sizes on the Seed Yield of Two Onion (Allium Cepa L.) Varieties (SAARC Journal of Agriculture, 2021)
An experiment was carried out at Horticulture Farm of Bangladesh Agricultural University, Mymensingh during the period from October 2018 to March 2019 to examine the effects of different bulb size viz., large size bulb (15±1 g), medium size bulb (10±1 g), small size bulb (7±1 g) on seed production of two onion varieties (Taherpuri and Kalash Nagari). Significant variation observed in both varieties for most of the parameters based on onion bulb size. The variety Kalash Nagari showed better performances compared to variety Taherpuri. After 60 days of planting, Kalash Nagari variety gave the highest plant height (55.07 cm), number of leaves (20.62), stalk length (100.78 cm), and total seed yield (630 kg ha-1), while in Taherpuri plant height, leaf number, stalk length and total seed weight were 32.21 cm, 6.93, 61.47 cm and 270 kg ha-1, respectively. Large sized bulb gave better performance compared to small sized bulb. The large sized bulb gave highest plant height (49.83 cm) and highest total seed yield (490 kg ha-1). Medium size bulb gave the seed yield (460 kg ha-1) and lowest in small size bulb (390 kg ha-1). Seed yield was significantly affected by the combined effects of variety and bulb size. Kalash Nagari onion with large sized bulb gave the highest seed yield (660 kg ha-1) and Taherpuri variety with small sized bulb gave the lowest seed yield (180 kg ha-1).SAARC J. Agri., 18(2): 51-65 (2020)